Anemia in Pregnancy and Its Maternal Perinatal Outcome - Indra Putra, Iriawan; Joice Margaretha Mathilda Sondakh; Juneke Joice Kaeng (Indonesian Socety of Obstetrics and Gynecology, 2024)
Objective: To investigate the relationship between anemia in pregnancy and maternal perinatal outcomes. Methods: This was a retrospective cohort study. This research was held at Prof. Dr. R. D. Kandou General Hospital Manado. Data was taken from January 2021 to December 2022. Results: There were 1953 deliveries which 1304 subjects (66.7%) with anemia 649 subjects with anemia (33.3%), 489 subjects with mild anemia, and 160 subjects with moderate-severe anemia. The median maternal age was 28 years for mild anemia. The majority of mothers have a high school education. A total of 326 study subjects were multigravidas with mild anemia. The results of severe preeclampsia with mild anemia were 30 subjects. Prolonged labor tends to be higher in the mild anemia group. The highest distribution was observed in the mild anemia group, with 12 cases of maternal mortality, 88 cases of premature birth, 78 cases of low birth weight (LBW), 75 cases of disorders leading to decreased scores, and 24 cases of fetal mortality. In research subjects, IUGR tends to be more common in groups with moderate-severe anemia with 14 subjects (8.8%). Hemoglobin levels showed a median of 11.6 g/dL with a distribution midway between 10.5 and 12.6 g/dL. The mean MCV value is 76.1 fL (SD 8 fL). The mean MCH value was 24.8 + 3.6 pg. The MCHC value is 32.5%. Conclusions: There are no significant relation in pregnant women with anemia with preeclampsia, prolonged labor, maternal mortality rate and IUGR, but there are significant relation between anemia in pregnancy with increase rate of caesarean section, premature delivery, low birth weight, low APGAR score and fetal death. Keywords: anemia in pregnancy, maternal outcome, neonatal outcome